Development of Somatic Embryo in Lithospermum erythrorhizon Siebb. et Zucc and The Study on The Effect of Methyl Jasmonate on its Maturation - Totik Sri Mariani; Octavia Ramayanti; Kazufumi Yazaki; Hiroshi Miyake (ANNALES BOGORIENSES, 2004)
A research on the somatic embryogenesis in Lithospermum erythrorhizol1 has been conducted. Embryogenic callus was inoculated in EIM9 liquid medium (modification ofLS medium), i.e. L2PVP (initiation medium) and the development of somatic embryo was observed. Ten J.1M and 100).lM methyl jasmonate was added into L3PVP medium (differentiation medium) for somatic emb yo maLUration. The purposes of this research were to observe tlle development of somatic embryo and to observe the effect of methyl jasmonate on maturation of the somatic embryo in L erylhrorhizol/ . The results showed that somatic embryogenesis in L erythrorhizon derived from single cells differentiated further forming proembryo, globular. heart, torpedo and cotyledon stage. Treatment with 10 f.1M and 100).lM methyl jasmonate induced maturation of somatic embryos (cotyledon stage) after transferring them to embryo development medium (L4PVP).